Metallographic examination of 16th century cannon material from the collection of Lviv History Museum - Shvachko, Sergey; Verkhoturova, Mariana; Pishatchin, Maria (Видавництво Львівської політехніки, 2017)
The article presents a detailed description of a16th century cannon from the collection of Lviv History Museum. It briefly looks at metallographic analysis techniques of cannon material. It describes metallographic examination of the 16th century cannon from the collection of Lviv History Museum. It makes a conclusion concerning a micro- and macrostructure of the 16th century cannon material from the collection of Lviv History Museum.
Keywords: the 16th century cannon; metallographic examination. iron; micro-; macrostructure; Lviv HistoryMuseum